A general fixed point theorem for two pairs of absorbing mappings in Gp-metric spaces - Popa, Valeriu (Annales Mathematicae Silesianae, 2020)
A general fixed point theorem for two pairs of absorbing mappings satisfying a new type of implicit relation ([37]), without weak compatibility in Gp-metric spaces is proved. As applications, new results for mappings satisfying contractive conditions of integral type and for ϕ-contractive mappings are obtained.